Multiple Screen Addiction and Impulsive Buying Behavior Among Selected Young Adults in Lemery, Batangas - Jervin Dinglasan Quicho; Trisha Mae J. Atienza; Ma. Christine Joyce L. Castillo; Cyrill P. Mendoza (Future Science / FSH-PH Publications, 2026)
This paper examined the correlation between multiple screen addiction and impulsive buying habit among young adults in Lemery, Batangas. With a descriptive-correlational design, 400 respondents aged 19-40 years were surveyed by use of Multiple Screen Addiction Scale (MSAS) and Buying Impulsiveness Scale (BIS). Findings indicated that a significant number of respondents had high scores of various screen addiction, especially in the areas of excessive screen time as well as compulsive digital behavior. Conversely, the majority of the respondents showed low to very low scores in impulsive buying behavior with none of them falling in the high and very high categories. Statistical results revealed that multiple screen addiction was moderately, positively and significantly correlated with impulsive buying behavior ( r = 0.387, p <.001), indicating that the higher level of screen addiction was, the more impulsive purchase decisions one had. These results implied that even though screen addiction was very common, not everyone would translate to high impulsive buying but it makes one more prone to it. To this end, the study offers community-based solutions like barangay digital detox programs, smart spending, and mentorship programs to ensure digital wellness and financial self-regulation. This research provided localized information on the multifaceted relationship between the utilization of technology and consumer behavior, and the importance of specific interventions to promote the establishment of healthier digital and financial practices in young adults.